2013
DOI: 10.1186/1471-2164-14-201
|View full text |Cite
|
Sign up to set email alerts
|

Xylem transcription profiles indicate potential metabolic responses for economically relevant characteristics of Eucalyptusspecies

Abstract: BackgroundEucalyptus is one of the most important sources of industrial cellulose. Three species of this botanical group are intensively used in breeding programs: E. globulus, E. grandis and E. urophylla. E. globulus is adapted to subtropical/temperate areas and is considered a source of high-quality cellulose; E. grandis grows rapidly and is adapted to tropical/subtropical climates; and E. urophylla, though less productive, is considered a source of genes related to robustness. Wood, or secondary xylem, resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 76 publications
(79 reference statements)
2
19
0
1
Order By: Relevance
“…Similarly, several expansins appeared to be expressed during the differentiation of Arabidopsis tracheary elements, while orthologs of AtEXPA1 and AtEXPA4 showed high expression in Eucalyptus xylem [31]. Colocalizations with IVNDFD QTLs were shown for two ␣-expansins out of five genes.…”
Section: ˛-Expansin Proteins Putatively Involved In Secondary Wall Fomentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, several expansins appeared to be expressed during the differentiation of Arabidopsis tracheary elements, while orthologs of AtEXPA1 and AtEXPA4 showed high expression in Eucalyptus xylem [31]. Colocalizations with IVNDFD QTLs were shown for two ␣-expansins out of five genes.…”
Section: ˛-Expansin Proteins Putatively Involved In Secondary Wall Fomentioning
confidence: 90%
“…Several ATPbinding cassette (ABC) transporters, which belong to a large multigene family, including indeed 128 genes in rice [26], are likely specifically involved in monolignol transports across membranes [27][28][29][30]. Other proteins are probably also involved, such as MATE (multidrug and toxic compound extrusion) efflux transporters because several family members were shown to be highly expressed in Eucalyptus xylem [31] . Colocalizations were shown with IVNDFD QTLs for two glucosyltransferase genes out of five, two ␤-glucosidase genes out of three, six ABC transporter genes out of 19, but not with any of the two MATE encoding genes.…”
Section: Ivndfd Qtl Colocalizations With Monolignol Biosynthesis and mentioning
confidence: 99%
“…Many structural and regulatory genes involved in cell wall formation have been reported [2]. Xylem transcription profiles obtained using novel sequencing technologies in three Eucalyptus species revealed many genes for wood formation [3]. Most structural genes involved in lignin biosynthesis have been identified in many species, including in woody plants [4].…”
Section: Introductionmentioning
confidence: 99%
“…The much higher number of non-DE genes compared to DE genes is consistent with findings of Thavamanikumar et al (2014) in xylem of E. nitens, and may be at least partly attributable to housekeeping genes that are constitutive genes required for the maintenance of basic cellular function and are expressed at relatively constant levels. Nevertheless such a low proportion of DE genes in our experiment was not expected given the natural differential expression existing between the urophylla and grandis parental species (Salazar et al, 2013), the disturbance in the regulation of gene expression often observed in interspecific hybrids (Hegarty et al, 2008) notably concerning the trans-regulatory mechanisms, the possible allele-specific expression mechanism (Song, 2016), and the open field cultivation conditions.…”
Section: Genotypic Effect On Transcript Abundance Between Genotypesmentioning
confidence: 57%
“…From the past 15 years, many genomic resources have been produced, culminating with the recent sequencing of the Eucalyptus grandis (Myburg et al, 2014) which provides the research community a reference sequence. Transcriptomics in Eucalyptus, including E. grandis and its hybrids, has also increased exponentially with many recent studies on different tissues, at different maturity stages and between contrasted conditions (Camargo et al, 2014;Hefer et al, 2015;Liu et al, 2014;Mizrachi et al, 2010;Salazar et al, 2013;Villar et al, 2011;Vining et al, 2014). It generated a wealth of knowledge in terms of annotation and expression features.…”
Section: Genetic Effect In Leaf and Xylem Transcriptome Variations Ammentioning
confidence: 99%